Oden Southern Ocean 2008/2009 - Data Collected Onboard Icebreaker Oden - Oden Southern Ocean 2008/09 - Meteorological, Oceanographic and Ship Data Collected Onboard Icebreaker Oden during November 2008 through January 2009. - Swedish Polar Research Secretariat (Swedish Polar Research Secretariat, 2017)
Oden Southern Ocean 2008/09 was a cooperative effort of the Swedish Polar Research Secretariat and the National Science Foundation (NSF) in the USA.

It was the third season in a row icebreaker Oden worked in Antarctica. The basis of the cooperative effort was that NSF chartered Oden from the Swedish Maritime Administration and the Swedish Polar Research Secretariat to break an ice channel to the McMurdo Antarctic Station in the Ross Sea, allowing supply vessels to reach the station. As Oden sailed through the Southern Ocean, researchers had an opportunity to perform marine studies.

The marine research conducted during Oden Southern Ocean 2008/09 was interdisciplinary, and involved environmental chemistry, chemical and physical oceanography, climate research, epidemiology and evolutionary biology. The scientific findings from the expedition will play an important role in our understanding of the Antarctic system and its role in climate change. Its extreme climate and isolated location makes the Antarctic a unique platform for studying the Earth’s climatic, biological and geological evolution, and the environmental problems of the future.

This data set contains meteorological, oceanographic and ship data collected during the American-Swedish expedition Oden Southern Ocean 2008/09, which was an international research cruise using the icebreaker Oden. The expedition embarked from Gothenborg, Sweden on October 28 2008 and arrived in McMurdo Januari 2009.

Data include meteorological variables: Air temperature, Humidity, Wind direction/speed, Atmospheric pressure.

Oceanographic variables: Sea water temperature, Conductivity, Salinity and Sound velocity.

Ship data: Position, Speed, Course.

Further metadata on instrumentation and the individual variables can be found in the info file. Graphics and files describing the route are included in the package.

Quality Information:

Obviously erroneous data (e.g. negative air pressure) have been omitted. No other processing or quality check of the data has been undertaken. Users should be aware of this in further data handling and analysis.

Oden Southern Ocean 2008/09 var ett samarbete mellan Polarforskningssekretariatet och det amerikanska forskningsrådet National Science Foundation, NSF.

För tredje säsongen i rad arbetade isbrytaren Oden i antarktiska vatten. Grunden för samarbetet var att NSF chartrade Oden av Sjöfartsverket och Polarforskningssekretariatet för att bryta en isränna till den amerikanska Antarktisstationen McMurdo vid Rosshavet, för att möjliggöra transporter till och från stationen. I samband med att Oden åkte genom Södra ishavet fick forskarna möjlighet att göra marina undersökningar.

Den marina forskningen som bedrevs under Oden Southern Ocean 2008/09 var tvärvetenskaplig och involverar miljökemi, kemisk- och fysisk oceanografi, klimatforskning samt epidemiologi och evolutionär biologi. Forskningsresultaten från expeditionen är en viktig del i förståelsen av framtida klimatutveckling. Det extrema klimatet och det isolerade läget gör att Antarktis miljö är unik. Här kan vi lära om jordens utveckling och morgondagens miljöproblem.

Oden lämnade Göteborg den 28 oktober 2008 och ankom till Montevideo, Uruguay, i slutet av november. I Montevideo bunkrade Oden olja och andra förnödenheter inför resan till Antarktis. Där gick även de 26 svenska och amerikanska deltagande forskarna, lärarna, teknikerna och expeditionsledningen ombord.

Utöver de 15 dygn som överfarten från Sydamerika tar, avsattes 20 dygn extra för forskning. Det innebar att forskarna hade mer än en månad till intensivt arbete med provtagningar i luft, is, ytvatten och djupvatten. Oden nådde den amerikanska forskningsstationen McMurdo i början av januari 2009 och expeditionsdeltagarna flögs sedan därifrån till Nya Zeeland och vidare hemåt. Oden återvände till Sverige i april 2009.

This data set contains meteorological, oceanographic and ship data collected during the American-Swedish expedition Oden Southern Ocean 2008/09, which was an international research cruise using the icebreaker Oden. The expedition embarked from Gothenborg, Sweden on October 28 2008 and arrived in McMurdo Januari 2009.

Data include meteorological variables: Air temperature, Humidity, Wind direction/speed, Atmospheric pressure.

Oceanographic variables: Sea water temperature, Conductivity, Salinity and Sound velocity.

Ship data: Position, Speed, Course.

Further metadata on instrumentation and the individual variables can be found in the info file. Graphics and files describing the route are included in the package.

Quality Information:

Obviously erroneous data (e.g. negative air pressure) have been omitted. No other processing or quality check of the data has been undertaken. Users should be aware of this in further data handling and analysis.
Oden Southern Ocean 2008/2009 - Datainsamling ombord på isbrytaren Oden - Oden Southern Ocean 2008/09 - Meteorological, Oceanographic and Ship Data Collected Onboard Icebreaker Oden during November 2008 through January 2009.
Keywords: Meteorology; Meteorologi; OCEANS; OCEAN PRESSURE; WATER PRESSURE; OCEAN CHEMISTRY; OXYGEN; SALINITY; DENSITY; OCEAN TEMPERATURE; WATER TEMPERATURE; WATER DEPTH; SEAFLOOR TOPOGRAPHY; BATHYMETRY; The icebreaker Oden; Isbrytaren Oden; Environmental Sciences; Miljövetenskap; Meteorology and Atmospheric Sciences; Meteorologi och atmosfärsvetenskap; Oceanography, Hydrology and Water Resources; Oceanografi, hydrologi och vattenresurser; Engineering and Technology; Teknik; Climatology / Meteorology / Atmosphere; Klimatologi och meteorologi; Oceans; Kust och hav